Effectiveness of preventative maintenance for reinforced concrete bridges - A stochastic approach - Tantele, Elia; Onoufriou, Toula; Mulheron, Mike J. (My University, 2005)
The effective allocation of resources and prioritisation of maintenance actions for ageing infrastructure systems is an important issue. There are many uncertainties in the decisions making process which may be associated with the deterioration prediction or the effect of various actions on the performance of a system. Such uncertainties if not addressed can lead to incorrect decisions and wastage of resources. This paper examines the issue of effectiveness of preventative maintenance (PM) on reinforced concrete bridges deteriorating due to chloride induced corrosion from de-icing salts. The uncertainties associated with corrosion initiation prediction and the effectiveness of various preventative maintenance actions are incorporated in a stochastic methodology presented in this paper. The proposed methodology was developed as part of a wider study which integrates this model within a proactive preventative maintenance strategy optimisation framework for RC bridges. The development of the stochastic PM effectiveness model is presented and discussed here together with an illustrative example.
Keywords: Concrete bridges; Maintenance; Reinforced concrete